Problematika Mahkamah Kehormatan Dewan Dalam Penegakan Etika Parlemen (Studi Komparatif Lembaga Etik Di Indonesia) - Rizki Andi Santoso; Naufal Itsnain Amirulazka; Reinhard Valent Siatiman; Naira Rayyana Firdaus; Frederica Karyadi (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The Council of Honor (MKD) as the institution that enforces the code of ethics for members of the House of Representatives is a crucial instrument in maintaining the dignity and integrity of the Indonesian parliament. Normatively, the MKD is regulated in Law Number 17 of 2014 concerning MD3, but the membership design, which is entirely derived from DPR factions, creates a high potential for conflict of interest, making the ethical enforcement process susceptible to internal political interests. In addition, the provisions of Article 132 paragraph (1) of the MD3 Law, which stipulates that MKD hearings are closed, have created an inconsistency with Article 5 paragraph (2) of DPR Regulation No. 1 of 2015 concerning the Code of Ethics, which emphasizes that members of the DPR must be willing to be monitored by the public. This study aims to examine the structural and normative weaknesses of the MKD in enforcing the ethics of DPR members. The research method used is normative juridical with a legislative, conceptual, and comparative approach by comparing the MKD with other ethical institutions such as the DKPP, the Honorary Council of Judges, and the Honorary Council of Notaries. The results of the analysis show that the MKD as an ethical institution is still vulnerable to political intervention and conflicts of interest due to its membership structure and normative regulations related to the conduct of hearings that are contradictory. In addition, the suboptimal imposition and execution of decisions have resulted in weak public trust in the MKD. Thus, it is necessary to reformulate regulations related to the MKD through open hearings, restructuring membership based on independent elements, and strengthening the execution of decisions without dependence on political decisions made in plenary sessions.